Comparison of endothelial function and sympathetic nervous system activity along the glucose continuum in individuals with differing metabolic risk profiles and low dietary sodium intake. Issue 1 (25th March 2019) - Baqar, Sara; Straznicky, Nora E; Lambert, Gavin; Kong, Yee Wen; Dixon, John B; Jerums, George; Ekinci, Elif Ilhan; Lambert, Elisabeth
Abstract : Objective: Low sodium intake may trigger sympathetic nervous system (SNS) activation and endothelial dysfunction. Studies have not explored these associations along the glucose continuum. Accordingly, we compared endothelial function and SNS activity in individuals with low sodium intake and differing categories of metabolic risk along the glucose continuum. We hypothesized that low sodium intake is associated with (1) impairment of endothelial function and (2) higher SNS activity in individuals with higher metabolic risk. Research Design and Methods: In this prospective observational study, participants (n=54) with low sodium intake (single 24 hours urine sodium excretion <150 mmol/24 hours) were categorized based on oral glucose tolerance testing as: normal glucose tolerance (NGT, n=10), impaired glucose tolerance (IGT, n=15), treatment naive type 2 diabetes (T2D−) (n=12) or treated type 2 diabetes (T2D+) (n=17). We assessed endothelial function using pulse amplitude tonometry (PAT) derived reactive hyperemic index and PAT ratio; arterial stiffness via augmentation index; muscle sympathetic nerve activity (MSNA) using microneurography; cardiac baroreflex; heart rate; blood pressure; glycosylated hemoglobin A1c (HbA1c) and lipid profile. Results: Mean (SD) sodium excretion was 110.6 (26) mmol/24 hours. Compared with NGT, IGT and T2D−, the T2D+ group had lower MSNA (p=0.005), PAT ratio (p=0.04) and baroreflex sensitivity (p=0.0002) and an augmented heart rate (p=0.02). The T2D+ group had appropriate mean (SD) glycemic (HbA1c 7.2 (1.72)%), total cholesterol (4.2 (1.0) mmol/L), low-density lipoprotein (2.2 (1.0) mmol/L) and blood pressure (systolic 136 (13), diastolic 78 (12)) (mm Hg) control. Conclusions: Individuals with T2D+ have impaired endothelial and baroreflex function, despite low sodium intake, appropriately managed cardiometabolic risk factors and lower SNS activity, compared with others along the glucose continuum. Whether low sodium intake is associated with modulation of the sympathovascular profile in T2D requires further investigation.